KAJIAN TENTANG PENERAPAN PRINSIP SYARIAH OLEH BANK SYARIAH DI DAERAH ISTIMEWA YOGYAKARTA - Abdul Fatakh (UIN Siber Syekh Nurjati Cirebon, 2020)
This research aimed to know the consistency of syariah principle implementation by Syariah Bank at Daerah Istimewah Yogyakarta, and the balance of responsibility between creditor and debtor in the case of credit mudharabah financing of customer or problematical financing.This juridical normative and sociological research was based on the bibliography study that supported by field research. The primary and secondary data were used in this study. The method of data collection was random sampling, which conducted by interviewing some respondents then used the qualitative descriptive method to analyses the data.The results of this research pointed that: firstly, it was not really consistent in The Consistency of Syariah Principle Implementation by Syariah Bank at DI. Yogyakarta because the products implementation did not use the classical syariah principle but the standard agreement of Indonesia Bank although it has placed carefulness principle forward; secondly, it was not adequately distributed in implementing of syariah banking products and without the social responsibility to the poor people; thirdly, it had not a special regulation on the syariah banking, therefore the existence of the regulation was not strong enough, because it still used the UU RI No.21 2008, the revision of UU RI. No. 10, 1998, the revision of UU RI, No. 07, 1992 about common banking and the operational regulation was controlled by Indonesia Bank Regulation (IBR), the resolution of civil conflict of banking still based on the certainty of Civil Code; fourthly, the administration financing same as the commonly and conventional bank, and the share of revenue based on the revenue sharing, not profit and loss sharing; fifthly, the responsibility of debtor’ business risk who experienced the problematical mudharabah financing, obliged to overcome the problem until she/he could payback the credit and the profit of revenue share and the creditor responsible to support the effort. When it could not to resave, then the debtor was assumed character risk based on the agreement of two parts, and the responsibility of debtor who character risk should to payback the main capital to creditor as the owner with the share revenue profit, based on the losses which happened because of the willful negligence and everything that opposite to the agreement. When the debtor could not payback the debt, the creditor has a right to sell the guarantee, that functions as the certainty of debtor to repay his/her debt over the mudharabah financing.